Ethics Related to the Adoption of Generative AI in Journalism - Situmorang, Ria Theresia (Universitas 17 Agustus 1945 Surabaya, 2024)
Media and content companies around the world are increasingly adopting generative AI technologies in text and image production to improve work efficiency. This article seeks to analyze the impact of ethical concerns that often arise in research on journalism and its relation to generative AI and identify areas that require more attention from a human-machine communication perspective. Based on the analysis of 14 articles, commentary and essay published in academic journals from 2022 to June 2024, the following key themes were identified: 1) Bias; 2) Misinformation; 3) Copyright; 4) Accuracy; and, 5) Credibility as well as other matters such as 6) Media autonomy; also 7) Replaceable human jobs. There were very few publications related to transparency. In addition, the majority of publications identified in previous studies lack diversity in sample selection as they are concentrated on the global north. There is a need for more inclusive practices in the global south with a social and cultural approach. This will help close the research gap and developers of generative AI-based technologies can consider diverse data sources when designing tools to minimize long-term risks.